PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM - Setiyono, Erik; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the influence of financial performance and firm size to the stock return. The dependent variable is the stock return. Meanwhile the independent variables are Firm Size and Financial Performance which have been measured by using Current Ratio (CR), Debt to Equity Ratio (DER), Return on Asset (ROA), and Earning per Share (EPS).The population is property and real estate companies which are listed in Indonesia Stock Exchange (IDX) in 2012-2014 periods. The sample collection technique has been done by using purposive sampling method, so that 32 property and real estate companies which are listed in Indonesia Stock Exchange (IDX) have been selected as samples. The data analysis technique has been done by using multiple linear regressions analysis with SPSS 20. The classic assumptiontest has been carried out before the multiple linear regressions analysis.Based on the result of hypothesis test, it shows that Debt to Equity Ratio (DER) and Earning Per Share (EPS) have positive influence to the Stock Return, meanwhile Current Ratio (CR), Return On Asset (ROA), and Firm Size does not have any positive significant influence to the stock price.Keywords : Financial Ratio, Firm Size, Stock Return.